Since that is a triangle the expression would be b x h / 2. So 12*12 = 144 / 2 = 72. The answer is 72.
Answer:
Step-by-step explanation:
= (x^2 + h^2 - 2xh) + (y^2 + k^2 - 2yk) As, (a-b)^2 = a^2 + b^2 - 2ab
= x^2 + h^2 - 2xh + y^2 + k^2 - 2yk
Answer:
4.589×10to the power of -11
Step-by-step explanation:
Answer:
(x - 1) and (x + 4)
Step-by-step explanation:
Given the zeros of a polynomial, say x = a, x = b then the factors are
(x - a), (x - b) and the polynomial is the product of the factors, that is
f(x) = (x - a)(x - b)
Here the zeros are x = 1 and x = - 4, thus the factors are
(x - 1) and (x - (- 4)), that is (x - 1) and (x + 4)
if you make a graph and add the coordinates on the graph you can use that find out how it creates a ratio of 1:2